Development Of Multimedia Ict-Based Online Learning (Cai, Cbi, Mobile Learning And E-Learning) In The Age Of Industrial Revolution 4.0 And Society 5.0 - Anam, Nurul (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
The purpose of this study is to describe the development of online learning based on Multimedia ICT in the Industrial Revolution Age 4.0 and Society 5.0. This research method uses a qualitative method with the type of library research. The results of the study indicate that as part of the effort to reform learning is to take advantage of ICT in learning activities. One of the ICT products that can be used in learning is a computer or laptop/netbook, an Android cellphone and the Internet. By applying ICT-based learning, students can learn "from" and "with" ICT products. Learning "from" ICT products is carried out using ICT-based learning such as from products in the form of CAI, CBI, Mobile Learning and E-Learning. Learning "with" technology is the use of technology as cognitive tools and the use of technology in a constructivist learning environment. Thus, the role of ICT-based multimedia in learning is becoming increasingly significant today, because these media are designed to complement each other so that the desired learning objectives will be achieved properly.